Problems of women's education in Turkestan in the 19th century - Zebuniso Akhrorova (International Journal of Advanced Science and Technology, 2020)
This paper makes analyses of the problems of women's education in Turkestan in the 19th century. Onthis case, research has accentuated on Turkestan, and investigations were followed in thecomparisons of 19th century. Finally it has concluded with the vivid analyses of the women'seducation in Turkestan in the 19th century.